Understanding the unique mechanism of ferroptosis: a promising therapeutic target - Kong, Yuanyuan; Li, Jing; Lin, Rufeng; Lu, Shifeng; Rong, Liucheng; Xue, Yao; Fang, Yongjun (Frontiers in Cell and Developmental Biology, 2024)
Ferroptosis is an iron-dependent form of regulated cell death and is characterized by high concentrations of intracellular lipid peroxide and a redox imbalance in the cells. Ferroptosis shows distinct morphological and biological features compared with other prominent mechanisms of programmed cell death. The distinct characteristics of ferroptosis include the dysfunction of the lipid peroxide repair enzyme glutathione peroxidase 4, the presence of ferrous iron overload, and the lipid peroxidation of polyunsaturated fatty acids. Several other metabolic pathways (including iron, lipid, and amino acid metabolism) and ferritinophagy, as well as transcription factors, can modulate ferroptosis. However, to date, the molecular mechanism of ferroptosis has not been elucidated. This review outlines the discovery, characterization, regulatory mechanisms, and crosstalk of ferroptosis.Further, we have noted the controversial elements in the ferroptosis-related mechanisms. Our inferences may provide a partial reference for developing strategies to regulate ferroptosis.